If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = i * 9 Reorder the terms for easier multiplication: 6 = 9i Solving 6 = 9i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-9i' to each side of the equation. 6 + -9i = 9i + -9i Combine like terms: 9i + -9i = 0 6 + -9i = 0 Add '-6' to each side of the equation. 6 + -6 + -9i = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -9i = 0 + -6 -9i = 0 + -6 Combine like terms: 0 + -6 = -6 -9i = -6 Divide each side by '-9'. i = 0.6666666667 Simplifying i = 0.6666666667
| 10x+15y=40 | | v=2*6 | | -8=15x-10 | | 2(x+6)=2x+6 | | 5=3r | | 19-2y-(6-4)(7y-2)+3y+15=0 | | X^2-5x-14*x-5=0 | | 21=8y-4 | | .4=16 | | c=2.2t^2-66t+655 | | .4=15 | | 2.1+10y=-7.9 | | 2(x-1)+6x=14 | | M^2=-m+20 | | x^2+y^2-10y-39=0 | | 6y+4x=-32 | | 4x+10=6x+14 | | (x-2)2+8=12 | | Y^2=15y-50 | | 3m+2+m+6+7m-16+3m=360 | | 4(4x+3)=60 | | 10-3x=4-2x | | Y^2=-9y-8 | | 4x^4-73X^3+28x^2+24x-45=0 | | 9x-2=-2(2x+4)-3(2x-2) | | a^2+11a-22=0 | | -16+5x=7(-6+8x)+3 | | 0=-16t^2+40t+2 | | (3i)(-2+6i)= | | 1x+.56=-.67 | | 5(x+3)+5=10 | | 52y=78 |